Impact of probiotic-enriched enteral nutrition combined with an ERAS protocol on postoperative recovery and metabolic rehabilitation in laryngeal cancer patients: a single-center retrospective cohort study - Wei, Xueqiong; Zhang, Xiaodong; Zeng, Junna; Chen, Shannan; Liao, Jun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPostoperative patients with laryngeal cancer frequently experience nutritional imbalance and complications due to restricted oral intake and inflammatory stress, and a single ERAS or nutritional strategy is insufficient for comprehensive recovery.ObjectiveTo evaluate the effect of probiotic-enhanced enteral nutrition combined with an ERAS nursing pathway on postoperative gastrointestinal function, inflammatory-nutritional response, and medical resource utilization in patients with laryngeal cancer.MethodsA total of 312 single-center laryngeal cancer cases from 2021–2024 were retrospectively enrolled. After 1:1 propensity-score matching, the experimental group (n = 132, probiotics + ERAS) was compared with the control group (n = 132, routine care). The primary outcome was time to first flatus. Secondary outcomes included inflammatory-nutritional indices, complications, hospital resources, and readmission. Statistical analyses used the Cox model, linear mixed-effects model, robust variance Poisson regression, Gamma-GLM, and Pearson correlation.ResultsOn postoperative days 1-3, energy and protein intake were significantly higher in the experimental group than in controls (both P< 0.001); a significant group × time interaction for 7-day cumulative target attainment was also observed (P< 0.001). The probability of first flatus increased by 98% (HR = 1.98 [1.55–2.52], P< 0.001). Within 72 h, rises in CRP, IL-6, and leukocyte count and declines in albumin and prealbumin were all significantly smaller in the experimental group (group × time interactions, all P< 0.001). Risks of Clavien-Dindo grade ≥ II complications, pneumonia, wound infection, and pharyngocutaneous fistula were markedly reduced (RR 0.25–0.39, P< 0.05). Median postoperative length of stay and antibiotic days fell by 3.21 and 2.48 days, respectively; cost ratio was 0.83 (0.79–0.88); 30-day readmission OR was 0.32 (0.12–0.83). ERAS adherence correlated inversely with length of stay (r = −0.59; β = −0.017; P< 0.001).ConclusionProbiotic-enhanced enteral nutrition combined with ERAS accelerates gastrointestinal recovery, suppresses inflammation, maintains nutritional status, and significantly reduces complications and healthcare burden in the perioperative period of laryngeal cancer, supporting the integrated “micro-ecology-nutrition-process” model as an effective strategy for rapid recovery in head-and-neck surgery.